Electric Cars For Dummies - Culp, Brian (For Dummies, 2022)
Drive into the 21st century in an electric car With falling cost of ownership, expanded incentives for purchasing, and more model and body type options than ever, it may finally be time to retire the old gas-guzzler and dive into the world of electric car ownership. Electric Cars For Dummies is your guide to becoming lightning powered, reducing your carbon footprint, and saving money on gas while you do it. This book teaches you how to select the battery-charged vehicle that fits your need and budget. It also offers insight into how to maintain your electric car, including answering all your questions about charging your vehicle. Calculate the total cost of ownership, prep your home to become one huge charger, and demystify the battery, the tune-ups and more. Learn the difference in cost of ownership and emissions between electric and gas-powered vehicles Explore your options and find an electric car that fits in your budget Know when and how to charge your vehicle, and what kind of maintenance it needs Figure out how to charge your car on the go This is the perfect book for new and would-be electric car owners looking for guidance on buying and maintaining one of these super sleek machines.